Conversion/alloying lithium-ion anodes – enhancing the energy density by transition metal doping. Issue 12 (1st October 2018) - Ma, Yanjiao; Ma, Yuan; Giuli, Gabriele; Diemant, Thomas; Behm, R. Jürgen; Geiger, Dorin; Kaiser, Ute; Ulissi, Ulderico; Passerini, Stefano; Bresser, Dominic
Abstract : Carefully selecting the transition metal dopant in consideration of its redox potential allows for further increased energy and power densities. Abstract : The development of alternative anodes is crucial for next generation lithium-ion batteries that can charge rapidly while maintaining high lithium storage capacity. Among the most promising candidates are conversion/alloying metal oxides like SnO2, for which, however, the irreversibility of the conversion reaction provides a great hurdle – not least with respect to the substantial charge loss and, thus, limited energy density. Herein, we report on the improved reversibility of the conversion reaction by incorporating a transition metal dopant like iron, cobalt, or manganese. While all these dopants provide substantially enhanced capacities due to their beneficial effect on the alloying and conversion reaction, a detailed comparison concerning the achievable capacity at lower voltages, i.e., less than 2.0 V, reveals that the careful selection of the dopant plays a decisive role for the achievable energy density on the full-cell level. In fact, the highest energy density is obtained when doping SnO2 with manganese rather than cobalt or iron because of its relatively lower redox potential and when setting the anodic cut-off to 1.5 V – despite the lower capacity. These results may serve as a general guideline when designing and evaluating alternatives for graphite – in particular, those including a conversion step.